Tumor subtypes and signature model construction based on chromatin regulators for better prediction of prognosis in uveal melanoma - Yue Li; Yue Li; Yue Li; Yue Li; Chao Xiong; Chao Xiong; Chao Xiong; Chao Xiong; Li Li Wu; Li Li Wu; Li Li Wu; Li Li Wu; et al. (Pathology and Oncology Research, 2023)
Background: Uveal Melanoma (UM) is the most prevalent primary intraocular malignancy in adults. This study assessed the importance of chromatin regulators (CRs) in UM and developed a model to predict UM prognosis.Methods: Gene expression data and clinical information for UM were obtained from public databases. Samples were typed according to the gene expression of CRs associated with UM prognosis. The prognostic key genes were further screened by the protein interaction network, and the risk model was to predict UM prognosis using the least absolute shrinkage and selection operator (LASSO) regression analysis and performed a test of the risk mode. In addition, we performed gene set variation analysis, tumor microenvironment, and tumor immune analysis between subtypes and risk groups to explore the mechanisms influencing the development of UM.Results: We constructed a signature model consisting of three CRs (RUVBL1, SIRT3, and SMARCD3), which was shown to be accurate, and valid for predicting prognostic outcomes in UM. Higher immune cell infiltration in poor prognostic subtypes and risk groups. The Tumor immune analysis and Tumor Immune Dysfunction and Exclusion (TIDE) score provided a basis for clinical immunotherapy in UM.Conclusion: The risk model has prognostic value for UM survival and provides new insights into the treatment of UM.